Milk Replacer Supplementation Ameliorates Growth Performance and Rumen Microbiota of Early-Weaning Yimeng Black Goats - Han, Zhaoqing; Li, Aoyun; Pei, Lulu; Li, Kun; Jin, Taihua; Li, Fukuan; Wang, Zhennan; Lv, Shenjin; Li, Yongzhu (Frontiers in Veterinary Science, 2020)
Increasing evidences indicated the ameliorative effect of milk replacer supplementation in ruminants for regulating their early growth and rumen development. However, it is still unclear that whether milk replacer supplementation has a beneficial role in the growth performance and rumen microbiota of Yimeng black goats (YBGs). Therefore, this study was performed to investigate the effects of milk replacer on growth performance and rumen microbiota of YBGs. Our results revealed that milk replacer supplementation could significantly improve the growth performance of YBGs. Additionally, the results of alpha and beta diversities indicated that there was no significant difference in richness and diversity between the control and milk replacer treated YBGs. At the phylum level, Bacteroidetes, Firmicutes and Proteobacteria were the most dominant phyla in all the samples at different stages. Moreover, the YBGs treated with milk replacer possessed higher abundance of Verrucomicrobia than that in the control YBGs, while the level of Actinobacteria was obviously decreased. It is noteworthy that the abundance of Proteobacteria in the control YBGs was higher than that in the YBGs supplemented with milk replacer throughout the experiment. At the level of genus, the differences in the richness between control and milk replacer supplement YBGs were gradually observed. Compared with the control YBGs, the proportion of Akkermansia, Veillonella, Anaerovibrio, Ruminococcaceae_NK4A214_group, Ruminococcus_1 and Ruminococcus_2 were increased in the YBGs treated with milk replacer, whereas Turicibacter was decreased. In conclusion, milk replacer supplementation may serve as a good applicant for ameliorating early YBGs development and rumen microbiota.